Slavery and the Everlasting Struggle for Selfhood in Toni Morrison’s Beloved(1987) - Djeridane, Azzedine; Mekhedmi , Okba; Kourdourli ,Abdelkader (Faculty of Letters and Foreign Languages Department of English, 2017)
Through fiction, Toni Morrison projects the history of the African Americans and their everlasting struggle to reach their authentic selfhood. This dissertation sheds light on the experience of African Americans’ journey to reach selfhood. Morrison’s Politzer winning novel Beloved, present the history of African American struggles in America, and how the changing and challenging societies influence the black individual’s attempt to reach his self-accommodation into family and society. African American individuals are vulnerable within their own home and society. Thus, this dissertation is devoted to the influence of the society, the mother, and the father in the development or destruction of African American individuals’s selfhood.